Effects of cigarette butts on marine keystone species (Ulva lactuca L. and Mytilus edulis L.) and sediment microphytobenthos. (April 2021) - Green, Dannielle Senga; Kregting, Louise; Boots, Bas
Abstract: Outdoor mesocosms with constantly flowing natural seawater were used to test the effects of littered cigarette butts on the filter feeder Mytilus edulis (blue mussel), the macroalga, Ulva lactuca (sea lettuce) and sediment microphytobenthos in a semi-natural marine setting. Either conventional, cellulose acetate, or biodegradable, cellulose, smoked cigarette butts were added at densities of 0.25 or 1 butt L −1 . The clearance rates of mussels exposed to 1 butt L −1 of cellulose acetate butts were three times less than the controls. The growth of U. lactuca was not measurably affected by cigarette butts, however the sediment chlorophyll content was significantly less in mesocosms exposed to 0.25 and 1 butt L −1 of cellulose acetate butts. These effects occurred despite constant replacement of seawater indicating how hazardous conventional cigarette butts are to marine life. Biodegradable cellulose cigarette butts had minimal effects on the measured variables but should still not be discarded as litter. Graphical abstract: Unlabelled Image Highlights: The impact of cigarette butts in a system with flowing water had not been tested. Outdoor marine mesocosms with sand, algae, mussels and flowing seawater were used. Smoked conventional or biodegradable cigarette butts L −1 were added to mesocosms. Conventional butts reduced filtration rates of mussels and chlorophyll in sand. Cellulose acetate cigarette butts pose a risk to marine ecosystems.